Evaluation Study of Critical Zones and Damaged Zones of Semarang City Groundwater Utilization Based on Geospatial Modeling - Widya Kurniawan; Tri Retnaningsih Soeprobowati; Fahrudin (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2026)
The Energy and Mineral Resources Office of Central Java Province has proposed the evaluation of the CAT Semarang-Demak groundwater conservation zone for the 2022 fiscal year. There it was announced that the evaluation in the Semarang-Demak Groundwater Watershed (CAT) in Semarang City, there is already a critical utilization zone (mera). Groundwater withdrawal, which tends to be more intensive over time, will have an impact on the quantity, quality, and carrying capacity of the local environment, and can lead to groundwater level subsidence and land subsidence. As an effort to fight and anticipate further environmental damage, groundwater management in Semarang City needs to be evaluated. This evaluation uses a geographic information system (GIS)-based approach method in making a spatial model of the damaged groundwater utilization zone in the Semarang City Groundwater Basin. This evaluation was carried out to determine the distribution and characteristics of the aquifer, hydrogeological conditions, groundwater and environmental conditions, groundwater protected areas, water needs for the community and its development. The results of the Evaluation, Mapping, and Analysis Study of Damaged Zones for Groundwater Utilization in Groundwater Catchment Areas in Semarang City can be used as a reference for the Central Java Provincial Government in making groundwater management policies according to its authority.